2017
DOI: 10.4103/1673-5374.206646
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent neuroprotective effect of enoxaparin on cold-induced traumatic brain injury

Abstract: Recent evidence exists that enoxaparin can reduce brain injury because of its anticoagulant activity. To investigate the potential therapeutic effect of enoxaparin on cold-induced traumatic brain injury, at 20 minutes after modeling, male BALB/c mouse models of cold-induced traumatic brain injury were intraperitoneally administered 3 and 10 mg/kg enoxaparin or isotonic saline solution. Twenty-four hours later, enoxaparin at 10 mg/kg greatly reduced infarct volume, decreased cell apoptosis in the cortex and obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Moreover, in experimental mouse models of ischemic stroke, enoxaparin seems to offer good neuroprotection and reduce ischemic lesion size by 49%. 34 Similarly, Yi et al 35 showed that LMWH improved outcome in a dose-dependent manner after stroke, as clinically confirmed at 6 months, and was more effective than aspirin alone in preventing early neurologic deterioration and improving the 6-month outcome in patients with ischemic stroke. However, Paula Muñoz-Venturelli et al 23 showed that patients who received subcutaneous heparin had greater major disability at 90 days.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in experimental mouse models of ischemic stroke, enoxaparin seems to offer good neuroprotection and reduce ischemic lesion size by 49%. 34 Similarly, Yi et al 35 showed that LMWH improved outcome in a dose-dependent manner after stroke, as clinically confirmed at 6 months, and was more effective than aspirin alone in preventing early neurologic deterioration and improving the 6-month outcome in patients with ischemic stroke. However, Paula Muñoz-Venturelli et al 23 showed that patients who received subcutaneous heparin had greater major disability at 90 days.…”
Section: Discussionmentioning
confidence: 94%
“…Growing evidence suggests enoxaparin sodium has the ability to accelerate neurologic recovery and greatly reduce cell apoptosis, inflammation, and edema in animals with induced TBI. 6,15…”
Section: Discussionmentioning
confidence: 99%
“…The brain injury was performed as previously described for a cryogenic trauma model (21,22).All the mice were anaesthetized with intraperitoneally (i.p.) ketamine (60 mg/ kg) and xylazine (6 mg/ kg) and fixed in the stereotaxic device.…”
Section: Cold Injurymentioning
confidence: 99%